Study on Failure Boundary of Thermal-scuffing for Heavy Duty Gear Transmission with Variable Speed and Variable Torsion - Jiqiang Li; Yanxin Li; Chao Chen; Liang Chen; Shidang Yan; Wei Ding (Jixie chuandong)
In view of the service characteristics of driving devices such as construction machinery， aerospace， rail transit and electric vehicle in the variable speed and variable torsion， the damage mechanism of thermal-scuffing failure for gear transmission is expounded， the multi factor coupling correlation relationship of thermal-scuffing is constructed， and the influences of transmission torque， gear speed， oil viscosity and oil temperature on the contact temperature for meshing tooth surfaces are analyzed， the corresponding design ideas to improve the thermal-scuffing load capacity is formed. At the same time， aiming at the combination of 18CrNiMo7-6 carburizing and quenching +ISO-VG 220 lubricating oil transmission gear， series of tests are carried out. The action weights of contact temperature and oil film thickness in thermal-scuffing analysis are determined. The value of failure boundary temperature for thermal-scuffing is also measured， the basis data for accurate evaluation on the gear thermal-scuffing bearing capacity in variable speed and variable torque in engineering application can be provided.